1967
DOI: 10.1530/acta.0.0560413
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATION OF 15α-Hydroxy-Oestriol FROM PREGNANCY URINE AND FROM THE URINE OF NEWBORN INFANTS

Abstract: From the extracts of enzyme-or acid hydrolysed pregnancy urine and urine of newborn infants a new oestrogen metabolite has been isolated.On the basis of the physical and chemical characteristics of this compound it is concluded that it is identical with 15\g=a\-hydroxy-oestriol(oestra\x=req-\ 1 , 3 , 5 ( 1 0 ) -t r i e n e -3 , 1 5 \ g = a \ , 1 6 \ g = a \ , 1 7 \ g = b \ -t e t r o l ) .It has been reported from this laboratory that one of the quantitatively most important metabolites of radioactive 17/5-oes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

1968
1968
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(14 citation statements)
references
References 13 publications
2
11
0
1
Order By: Relevance
“…This mass spectrum was identical with that of 15a-hydroxyoestriol silyl ether [13]. Table 3 shows the excreted amounts of steroids in urine from the pregnant women.…”
Section: Compound 26supporting
confidence: 52%
See 1 more Smart Citation
“…This mass spectrum was identical with that of 15a-hydroxyoestriol silyl ether [13]. Table 3 shows the excreted amounts of steroids in urine from the pregnant women.…”
Section: Compound 26supporting
confidence: 52%
“…The steroid monosulphate fraction contained two 15j3-hydroxylated pregnanolones; this is the first report of 15P-hydroxylated C,, steroids in the human. 1561-Hydroxylated neutral steroids [31,32] and oestrogens [13,33,34] as well as 15j3-hydroxylated oestrogens [35] have previously been isolated from human pregnancy urine but l5p-hydroxylated C,, steroids have not been described in mammalia. Schneider reported 15p-hydroxylation of 21-hydroxy-4-pregnene-3,2O-dione and regarded this as a biochemically "primitive" hydroxylation [36].…”
Section: Discussionmentioning
confidence: 99%
“…This natural hormone was discovered in urine of pregnant women by Diczfalusy and coworkers in 1965 [1]. Based on its physical and chemical characteristics it was concluded that E 4 is identical with 15α-hydroxyestriol (15α-OHE3) or estra-1, 3, 5(10)-triene-3,15α-, 16α-, 17β-tetrol [2]. Estetrol has the structure of an estrogenic steroid with four hydroxyl groups which explains the acronym E 4 .…”
Section: Introductionmentioning
confidence: 99%
“…During the same period, Diczfalusy and co-workers [5] succeeded in isolating and identifying the novel estrogen by extracting 200 L of late pregnancy urine. On the basis of physical and chemical characteristics they concluded that the compound was identical with 15␣-hydroxyestriol (15␣-OHE 3 ) or estra-1,3,5(10)-triene-3,15␣-,16␣-,17␤-tetrol.…”
Section: The Discovery Of Estetrolmentioning
confidence: 99%